Obliteration of gastric varices improves the arrival time of ultrasound contrast agents in hepatic artery and vein. Issue 9 (22nd August 2013) - Furuichi, Yoshihiro; Moriyasu, Fuminori; Sugimoto, Katsutoshi; Taira, Junichi; Sano, Takatomo; Miyata, Yuki; Sofuni, Atsushi; Itoi, Takao; Nakamura, Ikuo; Imai, Yasuharu
Abstract: Background and Aim: Liver cirrhosis (LC) is accompanied by hepatic arterializations, intrahepatic shunts, and hyperdynamic circulations. These changes shorten the arrival time (AT) of ultrasound contrast agents to the hepatic vein (HV). Whether treatment of gastric fundal varices (GVs) by balloon‐occluded transvenous obliteration (B‐RTO) improves the AT in LC patients was prospectively investigated. Methods: A total of 32 LC patients with GVs and 10 normal controls (NCs) were enrolled. This study was approved by the clinical research ethics committee. Images of hepatic artery (HA), portal vein (PV), and HV were monitored after an injection of a contrast agent using quantification software. The AT before and after B‐RTO in LC patients and that in NCs were compared. Results: All GVs were treated effectively, and indocyanine green retention rate was improved ( P < 0.0001). The mean values of the HA, PV, and HV ATs in the NCs were 21.9 ± 3.3, 28.2 ± 2.0, and 40.5 ± 2.1 s, respectively. Those in LC patients were 17.4 ± 4.4, 21.9 ± 5.6, and 26.3 ± 6.7, respectively, which were shorter than those in NCs ( P < 0.01, P < 0.002, P < 0.0001, respectively). However, these ATs were significantly prolonged 1 week after B‐RTO, with mean values of 18.7 ± 4.8, 23.8 ± 6.0, and 30.0 ± 7.2 s ( P = 0.043, P < 0.01, P < 0.001). Conclusion: Obliteration of GVs shifted the AT in LC patients to the normalization, raising the possibility of improvement of arterialization and intrahepatic shunt.